Entre cores e clima: padrões globais de variação de melanina na plumagem em aves de rapina (Accipitriformes) - Aguiar, Isadora Cristina Müller de (2024)
Ecogeographical rules offer a global view of the different characteristics of species and their relationship with the environment. In particular, Gloger's complex rule predicts that species with dark coloration (eumelanic) are favored in warm, wet environments, while reddish coloration (pheomelanic) is favored in warm, dry environments. The order Accipitriformes includes the eagles, hawks, and vultures of the Old World, with wide global distribution and plumage made up exclusively of melanic pigments. In addition, the high degree of polymorphism in the group suggests a high speciation rate. In this research, we investigated whether the plumage coloration of accipitrids is associated with climatic variables, such as temperature and precipitation, and whether this association supports Gloger's complex rule. We combined a dataset of photographs of the back and belly of 136 species of accipitrids and extracted the coloration using the RGB color system. Our results partially support Gloger's complex rule for the dorsal region: species with dark plumage are present in humid and cold environments, and reddish species in dry environments. However, darker bellies are related to warm, dry environments, while reddish bellies are associated with dry, but not always warm, environments. Contrasting colorations between the back and belly can be observed in several taxa, suggesting that evolutionary mechanisms and selection pressures act on distinct areas of the species' bodies. Thus, we suggest that camouflage and thermoregulation influence species with an eumelanic back, while pheomelanic coloration favors camouflage in drier habitats. For the belly, there are no clear hypotheses about eumelanic speciesin dry environments. On the other hand, the pheomelanic coloration on the belly is also consistent with camouflage in dry areas.